Perspectives of time: a qualitative study of the experiences of parents of critically ill newborns in the neonatal nursery in North Queensland interviewed several years after the admission. Issue 5 (14th May 2019) - Ireland, Susan; Ray, Robin A; Larkins, Sarah; Woodward, Lynn
Abstract : Design: A qualitative study informed by grounded theory principles to explore the experiences of parents who had extremely preterm or babies with antenatally diagnosed life-threatening diagnoses who were cared for in a regional tertiary neonatal unit. The study was conducted when the child was old enough to be diagnosed with long-term neurodevelopmental or medical sequelae. Setting: North Queensland is a large area in Eastern Australia of 500 000 km 2, which is served by one tertiary neonatal unit. Participants: Seventeen families representing 21 extremely preterm babies and one baby with congenital malformations who was not expected to survive prior to delivery (but did) were interviewed using grounded theory principles. Interviews were coded and themes derived. Results: Parents who recollect their neonatal experiences from 3 to 7 years after the baby was cared for in the neonatal intensive care described negative themes of grief and loss, guilt and disempowerment. Positive enhancers of care included parental strengths, religion and culture, family supports and neonatal unit practices. Novel findings included that prior pregnancy loss and infertility formed part of the narrative for parents, and hope was engendered by religion for parents who did not usually have a religious faith. Conclusions: An understanding of both the negative aspects of neonatal care and the positive enhancers is necessary to improve the neonatal experience for parents. Parents are able to contextualise their previous neonatal experiences within both the long-term outcome for the child and their own life history.